Lessons From Immune Checkpoint Inhibitor Trials in Hepatocellular Carcinoma - Mohr, Raphael; Jost-Brinkmann, Fabian; Özdirik, Burcin; Lambrecht, Joeri; Hammerich, Linda; Loosen, Sven H.; Luedde, Tom; Demir, Münevver; Tacke, Frank; Roderburg, Christoph (Frontiers in Immunology, 2021)
The implementation of immune checkpoint inhibitors (ICI) into the clinical management of different malignancies has largely changed our understanding of cancer treatment. After having proven efficacy in different tumor entities such as malignant melanoma and lung cancer, ICI were intensively tested in the setting of hepatocellular carcinoma (HCC). Here they could achieve higher and more durable response rates compared to tyrosine-kinase inhibitors (TKI), that were sole standard of care for the last decade. Most recently, ICI treatment was approved in a first line setting of HCC, for cases not suitable for curative strategies. However, only a subset of patients benefits from ICI therapy, while others experience rapid tumor progression, worsening of liver function and poor prognosis. Efforts are being made to find immune characteristics that predict tumor responsiveness to ICI, but no reliable biomarker could be identified so far. Nevertheless, data convincingly demonstrate that combination therapies (such as dual inhibition of PD-L1 and VEGF) are more effective than the application of single agents. In this review, we will briefly recapitulate the current algorithms for systemic treatment, discuss available results from checkpoint inhibitor trials and give an outlook on future directions of immunotherapy in HCC.